GAS CHROMATOGRAPHY–MASS SPECTROMETRY ANALYSIS OF BIOACTIVE COMPOUNDS IN ESSENTIAL OILS OF LEAF OF EUODIA SUAVEOLENS SCHEFF - SIDHARTA, BOY RAHARDJO; ATMODJO, PATRICIUS KIANTO (International Journal of Current Pharmaceutical Research, 2020)
Objective: Essential oils extracted from the leaf of Euodia suaveolens have been reported. However, there is no published data on comprehensive report on the chemical constituents of the essential oils and the methods utilized to extract the essential oils from the plant. This research aimed to reveal and determine the chemical constituents of essential oils from the leaf of E. suaveolens. Methods: Essential oils of leaf of E. suaveolens were extracted by steam distillation and were analyzed utilizing Gas Chromatography-Mass Spectrometry (GC-MS) methods. Results: The GC-MS analysis revealed the presence of twenty-five different chemical constituents from the essential oils. The main chemical constituents of essential oils extracted from E. suaveolens’ leaves were as follows menthofuran (50.38 %), p-mentha-1,8-diene (14.34 %), limonen (10.99 %), evodone (5.55 %), α-curcumene (4.65 %), globulol (1.88 %), longipinenepoxide (1.66 %), and linalool (1.40 %). This present research found three compounds, namely p-mentha-1,8-diene, globulol, and longipinenepoxide that have never been reported by any researchers working with this plant. Conclusion: The results showed that E. suaveolens contains essential oils that are potential to be explored further and utilized as medicinal products against some ailments.